Strategi Pengembangan Usaha Poultry Shop : (Studi Kasus: Garuda PS Payakumbuh) - Gita Pratiwi Ramadhan; Amsah Hendri Doni (Transformasi: Journal of Economics and Business Management, 2024)
This research aims to analyze and find out the Poultry Shop Business Development Strategy at the Garuda Poultry Shop, Payakumbuh City. This research uses a qualitative descriptive approach, namely data analysis that is explanatory and data information that is linked to theories and concepts using primary data sources and secondary data. The data collection techniques used in this research were interviews, observation, library research and documentation. The data analysis techniques used are data reduction, data display, and SWOT analysis. The results of this research show that the Garuda PS store is located in quadrant I. Quadrant I is a favorable situation because of opportunities and strengths. The results of the SWOT matrix analysis show that the right strategy for the Garuda PS Store is the SO strategy. The SO strategy is, Maintaining good service, maintaining tested product quality and complementing the products sold. Strategy implementation and obstacles to strategy implementation, namely 1) Checking the product is carried out. The obstacle in implementing this implementation is that product checking is only done manually. 2) Providing the best service to customers, the obstacle in starting this is service costs which always increase. 3) Complementing the products sold with other products. The obstacle in implementing this strategy is the large number of items that are stockpiled. This research contributes to finding out the right development strategy for the development of the Garuda PS Store.